XYLANASE PRODUCTION FROM LOCAL BACTERIAL ISOLATE - & Al-Shamary, Al-Badran (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2019)
Seventeen local isolates of Bacillus were isolated from soil to produce extracellular xylanase under submerged fermentation process by using xylan as carbon sole source. All isolates were subjected to quantitative scanning to select the most efficient one. The highest activity of xylanase (2680u/ml) was obtained from isolate Bacillus sp RS1. The isolate identified by 16SrRNA gene sequence of Bacillus subtilis ( accuracy of 99%)which was matched with sequence of Bacillus subtilis VBN25 that recorded in Genebank under the Accession Number of MG027675.1.Extracted xylan from agricultural waste by acidic method(papyrus, sun flower stalks, Ibaa Wheat type, Furat wheat type and Abo Ghraib wheat type)were used as the substrate for xylanase production from Bacillus. The results showed that the papyrus gave the highest amount of xylan (187.6 µg/ml) as compared with that of the sun flower stalks, Ibaa Wheat type, Furat wheat type and Abo Ghraib wheat type(161.3, 161.6, 157.6, 157.2) µ g/ml respectively. The results indicated that the highest xylanase activity was 2800 u/ml produced by Bacillus subtilus when Papyrus xylan was used.